2022
DOI: 10.21037/tlcr-22-158
|View full text |Cite
|
Sign up to set email alerts
|

FDG PET and CT radiomics in diagnosis and prognosis of non-small-cell lung cancer

Abstract: Background: 18 F-FDG PET and CT radiomics has been the object of a wide research for over 20 years but its contribution to clinical practice remains not yet well established. We have investigated its impact versus that of only histo-clinical data, for the routine management of non-small-cell lung cancer (NSCLC).Methods: Our patients were retrospectively considered. They all had a FDG PET-CT and immuno-histochemistry (IHC) to assess PD-L1 expression at the beginning of the disease. A prognosis univariate and mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…Results very similar to ours were obtained by Hannequin et al [40] and Oliveira et al [43]. Hannequin et al showed that PET and CT radiomic features have intrinsic power to predict survival, but they do not significantly improve the prediction of OS and progression-free survival in different multivariate models, in comparison to stage and gender [40].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Results very similar to ours were obtained by Hannequin et al [40] and Oliveira et al [43]. Hannequin et al showed that PET and CT radiomic features have intrinsic power to predict survival, but they do not significantly improve the prediction of OS and progression-free survival in different multivariate models, in comparison to stage and gender [40].…”
Section: Discussionsupporting
confidence: 88%
“…Machine learning has been employed in the context of medical imaging for segmentation and malignancy characterization [31], in histopathology [32], and in the study of biomarkers [33]. Recent studies have begun to explore the potential role of machine learning networks in prognosis, applying machine learning models to predict OS in NSCLC, mainly integrating tumor stage with clinical factors showing promising results [34][35][36][37][38][39][40][41][42][43][44]. However, a possible research gap lies in the fact that although studies indicate the potential of radiomics to predict survival in oncological patients, the clinical settings and the most important radiomic variables for such prediction need to be better established.…”
Section: Discussionmentioning
confidence: 99%
“…The analysis of radiomic features ("radiomics") and use of machine learning might impact patient treatment and help improve clinical therapy assessment. A variety of recent studies has emphasized their capabilities for automated tumor detection and delineation, survival stratification or prediction of PD-L1 expression [10,11,12,13,14,15]. Qiao et al showed that a combination of PET and CT radiomic features derived from the primary tumor could noninvasively predict occult lymph node metastases [16].…”
Section: Introductionmentioning
confidence: 99%
“…Dondi et al recently emphasized the influence of the PET/CT scanner type on ML and radiomics in the classification of stage I and II NSCLCs [18]. Some authors question the robustness or suitability of radiomics for broad clinical use in their current state [11,18]. With these considerations, we decided to focus on imaging-based parameters that are easier to assess and less variable like SUV max , and the CT-derived lesion volume.…”
Section: Introductionmentioning
confidence: 99%
“…Hannequin et al ( 2 ) present the results of their retrospective study where positron emission tomography/computed tomography (PET/CT) and CT scan radiomic features fail to predict overall survival (OS) and progression-free survival (PFS) when compared to other traditionally used clinical variables, as gender and stage.…”
mentioning
confidence: 99%